IMPLEMENTASI PSIKOLOGI PENDIDIKAN DALAM MENINGKATKAN MOTIVASI DAN PRESTASI BELAJAR MAHASISWA DI STKIP PESISIR SELATAN: TINJAUAN LITERATUR - Handayani, Revi; S, Neviyarni; Afdal, Afdal; Sari, Filma Alia; Sefrinal, Sefrinal (STKIP Pesisir Selatan, 2025)
Low motivation can be seen in students' lack of active involvement in the learning process, their lack of initiative to access additional learning resources, and their difficulty managing time and developing independent learning strategies. However, educational psychology literature confirms that motivation plays a crucial role as a determining factor in learning success. Educational psychology plays an important role in understanding student learning, especially in relation to motivation and academic achievement. This article reviews the literature on how educational psychology principles enhance student motivation and learning outcomes at STKIP Pesisir Selatan. The review shows that intrinsic motivation, cognitive-based learning strategies, the lecturer’s role as facilitator, and a supportive learning environment significantly influence achievement. Practical applications of educational psychology through active learning, feedback, positive reinforcement, and effective classroom management can improve learning quality. This article aims to provide a conceptual foundation for further research and teaching practices in higher education.